Effects of double sintering on the properties of porous ceramic - Abd Rahman, Hamimah (2008)
This present work reports the fabrication of porous ceramic through thermal treatment of powder mixture of alumina and starch. The effects of double sintering on the properties of porous ceramic were investigated. The mixture was milled and then the dried powder below 63 m was sintered in powder form at 1100°C, 1200°C, 1300°C, 1400°C and 1500°C. Meanwhile, the second stage sintering at 1500°C was implemented after powder pressing. All sintering process was carried out for 2 hours. The mechanical and physical properties such as porosity, density, modulus of rupture and hardness have been analyzed. The modulus of rupture has risen up to 14.704MPa which has successfully improved it about five times higher compared to the strength for single sintered sample. Besides that, the hardness value for double sintered porous ceramic could be increased until 35.90HV. The results have proven that double sintering process able to improve the density, hardness and strength of porous ceramic significantly. These ceramic bodies may have a potential use in a wide range of applications due to an excellent combination of properties.